2020
DOI: 10.1177/0300060520966877
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management of pregnancies with positive screening results for rare autosomal aneuploidies at a single center

Abstract: Objective To review our experiences on clinical management of pregnancies with positive noninvasive prenatal testing (NIPT) results for rare autosomal aneuploidies (RAAs) at a single center. Methods We performed a retrospective study and reviewed data from 18,016 pregnancies undergoing NIPT at a single center in China from March 2017 to February 2020. Depending on the patient’s choice, women with positive screening results for RAAs underwent chromosomal microarray analysis for invasive prenatal diagnosis. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
(61 reference statements)
1
3
0
Order By: Relevance
“…In our case, the combined first-trimester screening and the NIPT already showed an abnormal result leading to an early diagnosis through amniocentesis. Previous studies on rare autosomal aneuploidies (RAAs) at NIPT showed that these results might suggest an increased risk of confined placental mosaicism (CPM) or fetal mosaic aneuploidy [6]. In our case, the fetus showed many of the previously described typical features of a trisomy 22 mosaic: being female, congenital heart disease, and intrauterine growth restriction [5].…”
Section: Discussionsupporting
confidence: 59%
“…In our case, the combined first-trimester screening and the NIPT already showed an abnormal result leading to an early diagnosis through amniocentesis. Previous studies on rare autosomal aneuploidies (RAAs) at NIPT showed that these results might suggest an increased risk of confined placental mosaicism (CPM) or fetal mosaic aneuploidy [6]. In our case, the fetus showed many of the previously described typical features of a trisomy 22 mosaic: being female, congenital heart disease, and intrauterine growth restriction [5].…”
Section: Discussionsupporting
confidence: 59%
“…Outcomes with an unremarkable course of pregnancy have been reported, linked to the chromosome involved, with particularly poor outcome for trisomies 15, 16 and 22, and a mostly favorable outcome for trisomy 7, the most frequent RAT found by NIPT [ 89 , 94 , 95 ]. Trisomy 16 is associated with severe intrauterine growth restriction (IUGR), pre-eclampsia and fetal anomalies.…”
Section: Cfdna-based Screening (Nipt) Other Than Chromosomes 21 18 and 13mentioning
confidence: 99%
“…In studies of cfDNA for RAA, the screenpositive rate ranges from 0.12% to 0.91%, depending on the population studied [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] . The rate is higher in "high-risk" populations variably defined as women with ultrasonographic anomalies and prior children with chromosomal abnormalities.…”
Section: Cfdna For Rare Autosomal Aneuploidymentioning
confidence: 99%
“…Among publications, including RAAs detected on cfDNA and confirmed with invasive testing, the PPVs range from 3.8% to 58% 11,[13][14][15][16][17][18][19][20][21][22][23][24][25] . In a recent systemic evidence-based review of cfDNA, Rose et al 4 performed a quantitative analysis of PPVs reported in 17 studies (published through March 2021) and calculated an overall PPV for RATs of 13.42%.…”
Section: Cfdna For Rare Autosomal Aneuploidymentioning
confidence: 99%